PENGARUH CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN SAMPO HIJAB CLEAR - Rezkya Shinta Maharani; Uju Suji’ah (Bajang Institute, 2022)
The study determined to know the influence of celebrity endorser (credibility, suitability, and attractiveness) to consumer purchase decisions. Data collection is done by distributing questionnaire to 100 viewers over special region of yogyakarta as a sample to study sample retrieval using a verifying sampling approach using data analysis techniques used is the linear regression test Simultaneous significance (f test), partial significance test (t test), and coeffisien determinations (test r2). Studies have produced findings that partial attractiveness (tests t) have significant impact on purchasing decisions, silmutaneous credibility. suitability and attractiveness (test f) has a significant impact on purchasing decisions. The coefficient results of the determination (r2) show credibility, suitability and attractiveness to 44.8% of consumer purchase decisions, while the remaining 55.2% are affected by other unexamined factors. As for the most effective variable coefficients on purchasing decisions, it’s an attraction variable (x3) by 4,271.